Taste disturbances following middle ear surgery - Gurung , U; Bhattarai , H; Shrivastav , RP (Journal of Institute of Medicine Nepal, 2010)
Introduction: Iatrogenic chorda tympani nerve (CTN) injury during middle ear surgery is quite common. The objective of ours study is to observe frequency & types of CTN injury during middle ear surgery and assess types of post-operative taste disturbances and their functional recovery. Methods: Patients who underwent middle ear surgery from 1st October 2005 to 1st January 2007 in Tribhuvan University Teaching Hospital were divided into 6 groups according to intraoperative CTN manipulation as; seen but not handled, handled but not stretched, stretched but intact, cut while stretching, cut while using burr and clean cut with scissors. Subjective assessment of taste disturbance was done after 2days & 2, 4 & 6 months post-operatively and categorized as altered taste sensation/metallic taste, tongue numbness and dry mouth. Results: Amongst 260 patients, CTN was seen but not handled in 52/260 (20%), handled but not stretched in 54/260 (20.75%), stretched but intact in 66/260 (25.38%), cut while stretching in 17/260(6.5%), cut while using burr in 29/260 (11.15%) and clean cut with scissors in 42/260 (16.15%) patients. Eleven out of 260 patients (4.2%) symptomatic amongst which 6/11 (54.5%) had altered taste sensation,4/11 (36.3%) had tongue numbness and 1/11 (9%) had dry mouth. Complete recovery occurred in 9/11 (81.8%) patients by 6 months. Conclusion: Though iatrogenic CTN injury was common during middle ear surgery, frequency of taste disturbance was comparatively less, commonest type of CTN injury being stretched but intact. The most common post-operative taste disturbance was altered taste sensation/metallic taste. Most patients recovered completely by 6 months. Functional recovery was earlier when CTN was preserved than when sectioned.